A relevância da administração estratégica de imagem associada ao marketing turístico para a aquisição de destinos: um estudo da cidade de São Paulo/SP - Silvério, Ana Paula Maiochi (2010)
This dissertation had the primary objective of analyzing the relevance of associating tourism marketing to strategic image management in acquiring destinations and furthermore explores the tourism image of the city of São Paulo, aiming at providing a verification method for the phenomenon studied and lending more credibility to the work. To that end, we performed a bibliographical review on tourism marketing and the image of destinations and presented a case study about the image of São Paulo based on the work developed by São Paulo Turismo, a tourism and events company in São Paulo/SP. The principal results show that a progressive increase in tourism in the global market implies a competitive situation among locations interested in developing tourism, so that the efficient marketing management of the activities becomes a prerogative given market competitiveness; the results also show that the destination's image is ever more relevant given its recognition as one of the most important aspects in the process of selecting a destination, as well as in satisfaction and possible repeat visits. The theme has become prevalent internationally as an important research subject and existing investigations show that external and internal factors are extremely important and influence a tourism destination's image perception; therefore the strategic management of the destination's image is essential in the tourism marketing process. The case study evidenced the interest on the part of the tourism company in the city of São Paulo in expanding the city's image to encompass leisure and entertainment, given that the image is currently essentially focused on business and work, which hinders the full development of tourism in the city